Building an Entrepreneurship Ecosystem in Higher Education Towards a Strong Entrepreneurial Intention - Ahmad Kultur Hia; Fa'uzobihi Fa'uzobihi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
The design diversity of entrepreneurial education ecosystems (EEE) significantly influences entrepreneurial intention. Further exploration is required to clarify the roles of attitude, subjective norm, and entrepreneurial self-efficacy as antecedents of entrepreneurial intention in various social contexts. This study investigates the role of the Entrepreneurial Education Ecosystem (EEE) in shaping entrepreneurial intention through attitude, subjective norm, and entrepreneurial self-efficacy. The research adopts a one-shot survey design for efficiency purposes, involving 400 students randomly selected using simple random sampling to minimize sampling bias. These participants were drawn from private universities in West Java and Banten. Inferential analysis was conducted using Structural Equation Modeling (SEM) with a covariant approach. The findings reveal that EEE indirectly influences entrepreneurial intention by impacting key mediators, highlighting significant implications for enhancing entrepreneurial education in Indonesia. This research provides new insights into the indirect role of EEE as a mediator through attitude, subjective norm, and entrepreneurial self-efficacy in shaping entrepreneurial intention holistically. By employing an integrative framework, the study combines the Theory of Planned Behavior (TPB) with the concept of the Entrepreneurial Education Ecosystem (EEE).